Miocene paleoceanography at Rockall Plateau site 982 - Keating, Ronan Stephen (author); Miller, Kenneth (chair); Wright, James D (member); Browning, James V (member); Rutgers University; School of Graduate Studies (2024)
The Miocene Epoch contains two juxtaposed end-member climate states beginning with the Miocene Climate Optimum (MCO) (17-14.8 Ma), the most recent interval of ice-free or near ice-free conditions, and ending with the abrupt establishment of a permanent East Antarctic Ice Sheet during the Middle Miocene Climate Transition (MMCT) (14.8-12.8 Ma). The North Atlantic plays an important role in global ocean water circulation and Earth’s climate and yet, relatively few sea surface temperature (SSTs) records have been generated for the Miocene in the subpolar North Atlantic. Biomarker (UK’37, TEX86) SST records at subpolar Ocean Drilling Program (ODP) Site 982 (57.5°N) yield SST estimates which indicate that surface waters in the high latitudes remained warm (>20°C) until ⁓8 Ma when 4°C cooling occurred. In contrast, foraminiferal-based estimates from subtropical and transitional DSDP Sites 563, 558, and 608 (33.6-42.8°N) indicate that the largest cooling (4°C) occurred during the MMCT between 14.8-12.8 Ma, recording little to no cooling after 8 Ma. We analyzed planktonic (G. bulloides and G. praebulloides) and benthic foraminifera (P. wuellerstorfi, S. tenuicarinata) from the Early to Late Miocene (20 to 4.5 Ma) at Site 982 for δ 18O and δ 13C to evaluate SSTs, thermocline and deepwater evolutions, and to test the biomarker-based reconstructions of SSTs in the subpolar North Atlantic. Our results show that planktonic foraminifera from Site 982 record a 1.45‰ increase in δ18O values between 15-13.8 Ma, reaching modern values by 11.75 Ma (1.55‰ Modern for G. bulloides). Accounting for ice volume difference using Miller et al. (2020) ice volume estimates, SSTs varied between 15-17°C during the MCO and cooled to 11-13°C with the MMCT, in line with the modern seasonal SSTs in the region (Modern winter 9°C, Modern Summer 13°C). Our benthic foraminiferal δ18O values record a 0.5‰ increase reflecting a 2-3°C deep-water cooling following the MCO. In contrast, the UK’37 and TEX86 based SSTs recorded modest cooling (<2°C) ...